Navigating identity, empowerment, and marginalization in a Turkish EMI terrain: the case of an international student - Ozdil, Busra Muge; Kunt, Naciye (Routledge Journals, Taylor & Francis Ltd, 2025)
This study explores how the linguistic repertoire of an international multilingual individual interacts with EMI to shape identity (re-)construction in academic and social contexts. Using a narrative inquiry approach, the researchers collected data through an autobiographical narrative, a follow-up interview and three unstructured meetings. English emerged as a powerful tool enabling the participant to transcend systemic barriers, gain academic capital, and cultivate a sense of belonging in a multicultural setting. However, the dominance of English and Turkish in academic and social spheres triggered feelings of exclusion and disconnection from her Arabic roots. Through reflective agency, the participant embraced her heritage by integrating Arabic into her academic pursuits and exploring culturally aligned fields of studies in her department. Her experiences underscore the need for inclusive language policies and translanguaging practices in EMI settings to address the fluidity of multilingual identities and foster equitable participation.
Keywords: Multilingualism; linguistic repertoire; EMI; identity; marginalization